Nationalism - Smith, Anthony D. (Cambridge Polity Press, 2010)
Debate still rages over some of the questions Doreen Massey provoked in the classic first edition of Spatial Divisions of Labor, such as the nature of theory, the importance of contingency and uniqueness, and the relationship of Marxism. This second edition addresses these controversies, and also reflects on other debates which have taken place over the last decade. It contains a new first chapter and a lengthy additional concluding essay in which Massey takes up the issues of the book's relation to Marxism, its position on explanation, its
Includes bibliographical references (p. [357]-361) and index.
Keywords: Nationalism